Nitrogen-doped single walled carbon nanohorns enabling effective utilization of Ge nanocrystals for next generation lithium ion batteries. (1st March 2019) - Gulzar, Umair; Li, Tao; Bai, Xue; Goriparti, Subrahmanyam; Brescia, Rosaria; Capiglia, Claudio; Zaccaria, Remo Proietti
Abstract: Among various carbon materials, nitrogen doped single walled carbon nanohorns (N-SWCNHs) have a unique structure of clustered conical cages (2–5 nm in diameter and 40–50 nm in length) arranged in dahlia, bud and seed-like configurations. Each conical cage has five pentagons at their tips which act as potential reactive site with their own distinct chemistry. We exploited these reactive sites of N-SWCNHs by preferentially growing germanium nanocrystals (Ge NCs) onto their conical tips using oleylamine as a mild reducing agent. Therefore, Ge decorated N-SWCNHs (Ge@N-SWCNHs) composite was used, for the first time, as active anode material for lithium ion batteries providing high and stable capacity of 1285 mAh/g at 0.1C after 100 cycles. Our results show that preferential growth of Ge Nanocrystals (NCs) on the tips of N-SWCNHs not only allows high utilization of active material but prevents the aggregation of Ge NCs after multiple cycling. Finally, we highlight the potential role of N-SWCNHs as cheap and industrially scalable conductive host for next generation lithium ion batteries. Graphical abstract: